BIOCHEMICAL PARAMETERS IN RELATION TO SERUM ALPHA FETOPROTEIN & LEPTIN LEVELS IN IRAQI PATIENTS WITH CHRONIC LIVER DISEASES: Life Science-Clinical Biochemistry - G. ZAINAL, DR. ISRAA; DR. SAFA A.A.; K.OBEAD , WAJEEH (International Journal of Life Science and Pharma Research, 2013)
Background: Hepatitis B and C virus is a leading cause of chronic liver disease. Elevated serum alphafetoprotein (AFP) has been used as a marker for hepatic regeneration after the destruction of hopatocyte in viral hepatitis. Also Leptin level may be important to determined in patients with chronic hepatitis B and C. Aims: This study aimed to examine the association between serum AFP, serum leptin levels and some other biochemical parameters in patients with chronic liver disease (B and C). Materials and methods: Serum AFP, leptin, total serum protein TSP ,lipid profile, transaminases, alkaline phophatase ALP, total serum bilirubin levels TSB were measured in 61 patients (31 HBV, 30 HCV) and compared with 30 control subject. Results: In comparison to controls, a significant increase in the serum AFP , Leptin, TSP, AST, ALT,ALP & TSB levels (p < 0.00) and a significant decrease in Albumin, cholesterol , Triglyceride, (HDL), (VLDL) & (LDL) levels (p < 0.00) compared to control subject. Also Serum AFP levels showed positive correlation with Prothrombin time (PT) (r=0.384, p=0.048) & with Leptin(r=0.531, p=0.005) in HBV patients. Conclusions: AFP and Leptin can be used as dependent predictors in Patients with HBV, HCV.